2016
DOI: 10.1038/leu.2016.359
|View full text |Cite
|
Sign up to set email alerts
|

EGR2 mutations define a new clinically aggressive subgroup of chronic lymphocytic leukemia

Abstract: EGR2 mutations in CLL 5 AbstractRecurrent mutations within EGR2 were recently reported in advanced-stage chronic lymphocytic leukemia (CLL) patients and associated with a worse outcome. To study their prognostic impact, 2403 CLL patients were examined for mutations in the EGR2 hotspot region including a screening (n=1283) and two validation cohorts (UK CLL4 trial patients, n=366; CLL Research Consortium (CRC) patients, n=490). Targeted deep-sequencing of 27 known/postulated CLL driver genes was also performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 57 publications
(54 reference statements)
2
43
0
Order By: Relevance
“…CLL4 represents an ideal candidate for such an analysis, with expansive clinical and biological description [8, 12, 13, 17, 21, 24, 26, 29, 31-33, 40, 41] and protracted clinical follow-up. Our study confirms previous studies incorporating samples from this patient cohort showing the impact of TP53ab on PFS and OS in MVA, SF3B1, EGR2 [25,26], RPS15 [1,24] and NFKBIE [25,28,42] mutations on OS in univariate analysis, with SF3B1 and EGR2 mutations retained as independent markers of OS in MVA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…CLL4 represents an ideal candidate for such an analysis, with expansive clinical and biological description [8, 12, 13, 17, 21, 24, 26, 29, 31-33, 40, 41] and protracted clinical follow-up. Our study confirms previous studies incorporating samples from this patient cohort showing the impact of TP53ab on PFS and OS in MVA, SF3B1, EGR2 [25,26], RPS15 [1,24] and NFKBIE [25,28,42] mutations on OS in univariate analysis, with SF3B1 and EGR2 mutations retained as independent markers of OS in MVA.…”
Section: Discussionsupporting
confidence: 90%
“…The trial demonstrated superior response rates and progression-free survival (PFS) for FC-treated patients compared with those patients treated with FDR or CHL. Previous genomic analysis of this trial has shown TP53 [8], SF3B1 [17], NOTCH1 (coding [17] and non-coding [21]), ATM plus del(11q) [12] and EGR2 [26] lesions to have prognostic significance in multivariate analysis (MVA) and of RPS15 [24] in univariate analysis. The importance of data from CLL4 may be questioned given the studies showing the superior efficacy of FC plus an anti-CD20 antibody (FCR) compared with chemotherapy alone, with the exception of patients with a NOTCH1 mutation [20], and emerging data suggesting the superiority of novel agents compared with chemotherapy-based regimens.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…This division between groups was used to perform the inter-group comparisons and the classification for the predictive analysis. The separation for the predictive analysis was made based on the assumption that, for the RNAseq analysis, patients with mutated EGR2 gene have a good prognosis [26] and, for the WES analysis, the patients with unmutated the IGVH gene are characterized as stable [27].…”
Section: Figure 1 Integrated Profile Creation Processmentioning
confidence: 99%
“…Several molecular studies have identified a set of genes, including NOTCH1, SF3B1 BIRC3, RSP15, and EGR2, as novel molecular biomarkers that account, at least in part, for chemorefractoriness in addition to TP53 disruption. These genetic aberrations appear to be mutually exclusive with disruption of TP53, at least in most cases, indicating that multiple alternative pathways can lead to CIT failure [11,[20][21][22][23]. In particular, in the case of FCR, mutations of BIRC3 (Baculoviral IAP Repeat Containing 3) stand out as a novel predictor of treatment failure.…”
Section: Molecular Abnormalities Of Patients Failing Citmentioning
confidence: 99%